“Evaluación de diferentes distancias de siembra en el cultivo de pepino (Cucumis sativus) con la aplicación de dos abonos orgánicos edáficos en el Recinto Chipe Hamburgo 2.” - Acosta Vera, Karla Jacqueline (2023)
The present investigation was carried out in the Chipe Hamburgo 2 enclosure, belonging to the El Triunfo parish of the La Maná canton, with the objective of evaluating different planting distances in the cultivation of cucumber (Cucumis sativus) with the application of two organic fertilizers edaphic in the Chipe Hamburgo 2 enclosure. A Completely Random Block Experimental Design was used, in a factorial arrangement of AxB (three planting distances, two edaphic organic fertilizers), in four repetitions. The variables under study were: Vegetative development variables: Plant height at 15, 30, 45 and 60 days, days to flowering, number of flowers, flower/fruit ratio. Among the production variables are: Number of fruits, length and diameter of fruits, fruit weight and agronomic yield. The following results were obtained: Higher plant height at 15 days with 23.23 cm, while at 30, 45 and 60 days T1 maintained the highest plant height averages with 55.35, 154.20 and 182.15 cm respectively, the lowest time to flowering maintained T5 with emission of flowers at 16.10 days, for the number of flowers the best results were obtained in T3 with 22.40 flowers, while the best flower/fruit ratio was presented in T5 with 1.17 flowers that were they will turn into fruits. In the T5 production variables have the best results with the highest number of fruits 11.70. In the same treatment, fruits were presented with a greater length and diameter of 27.80 cm and 6.92 cm respectively, for which a greater fruit weight was achieved in T5 with a total of 7.20 kg of harvested cucumber. The economic analysis T1 reached the highest production, with 44904.76 kg/treatment. For the net profit T3 it presented better indices with USD 7847.62. A better costbenefit ratio was obtained in T5 with USD 1.10 for each economic unit invested.